Precipitation Regime in South Part of Iran Studying of Iran - Farnaz Pourasghar; Saeed Jahanbakhsh; Behrooz Sari saraf; Hooshang Ghaemi; Masomeh Tadayoni (نشریه جغرافیا و برنامه‌ریزی, 2013)
This is a study of change in annual precipitation amounts and variability in southern part of Iran during 1974-2005. Southern part of Iran has been regionalized based on six factors in 183 stations using Principal Component Analysis (PCA) and Cluster Analysis (CA). The stations were grouped into four individual clusters. Topography and latitude play an important role in determining boundaries between identified subdivisions and existence of spatial differences between them as well. Spatial variability and relationship between the precipitation series at 183 of stations were investigated by principal component analysis. A PCA of annual precipitation reveals five components that account for 68% of the total variance. The annual precipitation PCs are controlled by atmospheric circulation. Analysis of the results revealed that annual precipitation in south part of Iran is mainly related to Sudan and Mediterranean wave.